Determinación de daño genotóxico en la población expuesta a pesticidas en ColaisacaCalvas - Carrion Carrion, Mayra Daniela (2018)
Abstract: In the present study, a monitoring of the genotoxic effects that pesticides can cause in the inhabitants of the Colaisaca parish, Calvas canton, Loja Province, Ecuador; using samples of scraping of buccal mucosa to verify if there is damage at DNA level by micronucleus test; and, blood samples to measure liver damage with enzymatic tests of TGO, TGP, ɣ-GT, ALP and ChE; the latter also assesses whether the SN is affected. The study population was 81 people; 54 individuals (29 exposed and 25 not exposed) corresponded to the female gender; and, of the masculine gender there were 27 individuals (15 exposed and 12 not exposed). In the test of micronuclei and AN of both genders, it was statistically significant, between the exposed and unexposed group, being more evident in women due to the 15-fold increase in micronuclei.